PENGARUH PENGETAHUAN DAN SIKAP TERHADAP PENINGKATAN PEMAHAMAN REMAJA TENTANG SADARI MELALUI PENYULUHAN VIDEO DI SMAN 2 TIMANG GAJAH - Deli Puput Lastari; Andi Pratama Putra; Saipullah; Nurlaely HS (Aceh Health Sciences Journal, 2026)
Breast cancer is one of the most common cancers among women worldwide, including in Indonesia. Early detection through Breast Self-Examination (BSE) is a simple, effective, and low-cost method to prevent late diagnosis. However, knowledge and attitudes of adolescent girls toward BSE remain limited. This study aimed to determine the effect of video-based health education on knowledge and attitudes regarding early detection of breast cancer among female students at SMAN 2 Timang Gajah. The research design was pre-experimental with a pretest-posttest approach. The population consisted of 176 students from grades X–XII, selected using total sampling. The instrument used was a structured questionnaire on knowledge and attitudes toward BSE. The results showed a significant increase in knowledge, with the mean score rising from 58.42 before the intervention to 79.21 after the intervention (p = 0.005). Similarly, a significant improvement in attitudes was found, with the mean score increasing from 75.40 to 78.15 (p = 0.000). In conclusion, video-based BSE education effectively improves knowledge and attitudes toward breast cancer early detection among female students. It is recommended that schools and health institutions strengthen health promotion programs using audio-visual media to encourage preventive behaviors from adolescence. Keywords: Breast Cancer, Knowledge, Attitude